ANALYSIS OF THE ROLE OF UMKM TO IMPROVE THE PROSPERITY OF THE COMMUNITY FROM THE PERSPECTIVE OF ISLAMIC ECONOMIC LAW (STUDY ON THE NATURAL TOURISM OF SUMBERINGIN, TUMPANG DISTRICT, MALANG REGENCY) - Rokiyah; Ane Fany Novitasari; Sri Hudiarini; Mohammad Sinal (International Journal of Economic Research and Financial Accounting, 2024)
The existence of MSMEs is expected to provide prosperity for owners and the surrounding community. Welfare can be understood as equal distribution of life at a higher level from life itself. However, this goal is not in line with the conditions at the Sumberingin Bathing Nature Tourism. The existence of these destinations has not been able to achieve the goals of MSMEs. The aim of this research is to analyze the concept and role of MSMEs for the welfare of society from the perspective of Islamic law (study of the natural tourism of Sumberingin baths, Tumpang District, Malang Regency). This research is empirical research. The research approaches used are the Analytical Approach and the Case Approach. Data collection for this research used library study techniques and the data that had been processed systematically was then analyzed descriptively and evaluatively. The research results showedthe concept of MSMEs for the welfare of society in the perspective of Islamic economic law, namelyfulfilling physical needs and halal sustenance and the blessings of sustenance received and creating a sense of security and love for others. Furthermore,The role of the Sumberingin Bathing Nature Tourism MSME is to improve the welfare of the community from the perspective of Islamic economic law, namely creating jobs, meeting economic needs and helping other people in need.Based on the results of an indicator survey that measures welfare from an Islamic economic perspective, it can be concluded that the majority of MSMEs feel that their needs are met, they are helped to obtain halal sustenance, they do business with a sense of security and peace.